Changes in sun protection behaviours, sun exposure and shade availability among adults, children and adolescents in New South Wales, 2003-2016 - Andre Ying‐Song Liew; Anne E. Cust (Elsevier, 2021)
Abstract Objective: To inform skin cancer prevention policies and campaigns, we investigated changes over time in sun protection behaviours, sunburn, sun exposure and shade availability in public spaces among people living in New South Wales (NSW), Australia, between 2003 and 2016. Methods: We analysed cross‐sectional data from the NSW Population Health Survey collected in 2003, 2007, 2014 and 2016, which included approximately 15,000 respondents of all ages in each year. Logistic regression models were used to analyse overall changes over time and for different age, sex and sociodemographic groups. Results: The use of sunscreen and protective clothing and the availability of shade increased between 2003 and 2016, but sunburn and sun exposure during peak times of ultraviolet radiation also increased. In subgroup analyses, there was no improvement in sun protection behaviours among adolescents and increases in sunburn and sun exposure were observed only among adults, particularly women and in areas with less social disadvantage. Conclusions: Sun protection behaviours have improved over time among some population subgroups, but over‐exposure to ultraviolet radiation remains prevalent. Implications for public health: Skin cancer prevention initiatives that specifically target adolescents and sun exposure during peak times are needed to help reduce population skin cancer risk.